An interdisciplinary synthesis of research on understanding and promoting well‐doing. Issue 9 (14th August 2022) - Lieder, Falk; Prentice, Mike; Corwin‐Renner, Emily R.
Abstract: People's intentional pursuit of prosocial goals and values (i.e., well‐doing) is critical to the flourishing of humanity in the long run. Understanding and promoting well‐doing is a shared goal across many fields inside and outside of social and personality psychology. Several of these fields are (partially) disconnected from each other and could benefit from more integration of existing knowledge, interdisciplinary collaboration, and cross‐fertilization. To foster the transfer and integration of knowledge across these different fields, we provide a brief overview with pointers to some key articles from each field, highlight connections, and introduce an integrative model of the psychological mechanisms of well‐doing. We identify some gaps in the current understanding of well‐doing, such as the paucity of research on well‐doing with large and long‐lasting positive consequences. Building on this analysis, we identify opportunities for high‐impact research on well‐doing in social and personality psychology, such as understanding and promoting the effective pursuit of highly impactful altruistic goals.